Arah Baru Reformasi Pendidikan dan Implementasi dalam Proses Keberlangsungan Pendidikan Nasional di Indonesia - Muhammad Nafi’uddin (Academia Publication, 2022)
This study aims to explore new directions of education reform and its implementation in strengthening the process of national education sustainability in Indonesia. This new direction of education reform includes several dimensions, namely. First, the expansion of access and equity in education; Second, curriculum strengthening; third, the use of relevant ICT in learning spaces. From this dimension, it is expected to be able to answer the demands of the times and industry needs in order to produce graduates who are ready to contribute actively in the world of work. The implementation of this new direction of education reform requires support from various parties, including the government, educational institutions, the community, and the business world. There needs to be synergy and collaboration to achieve common goals in advancing national education. In the Indonesian context, coordination between central and local governments is needed to ensure education policies are well implemented.